Discovery of Novel Enzyme Inhibitors from Nature via In vitro and In silico Methods - Orhan, Ilkay Erdogan (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Natural products are always important in finding new drug candidates and natural product chemistry research has been a mainstay in drug discovery and development. Enzyme inhibitors are known as one of the strongest therapy strategies against a wide range of diseases. In search of novel enzyme inhibitors from natural sources, mainly plants, many medicinal plants and pure natural compounds have been screened using microplate assays against a number of enzymes including cholinesterase family, elastase, collagenase, tyrosinase, xanthine oxidase, phosphodiesterase-I, carbonic anhydrase-II, lipoxygenase, HMG CoA reductase, and others. The active inhibitors found are further investigated by in silico methods using molecular docking experiments. Promising compounds such as coumarins and other polyphenolics including flavonoids have been identified as active inhibitors. Examples of natural products as promising enzyme inhibitors determined by this group will be underlined, with implications for anti-aging cosmetics as well as therapeutic applications.